PERILAKU AUDIT DISFUNGSIONAL: BUKTI EMPIRIS PERILAKU AUDITOR DI JAWA TENGAH DAN DIY - Alfi Rosa Mustika; Imam Ghozali (Diponegoro Journal of Accounting, 2016)
This study aims to determine the factors that affect turnover intention with dysfunctional audit behavior as an intervening variable. This study is a replication of the study conducted by Yuen et al. (2013). Factors examined in this study is time budget pressure, auditor’s independence, client importance and task complexity. This study was conducted by a survey of auditors working in Public Accounting Firm (KAP) of Central Java and Yogyakarta, especially in Semarang and Yogyakarta. Determination of the samples was done by convenience sampling method. The number of samples is 62 respondents. This research use Partial Least Square (PLS) approach on smartPLS 3.0 software. The study analyzed with path analysis.The results showed that time budget pressure, auditor independence, client importance and task complexity has positive relationship toward acceptance of dysfunctional audit behavior, and there is positive relationship between the acceptamce of dysfunctional audit behavior towards turnover intention. The results could help the firm to reduce the level of turnover intention and identify the factors that affect the dysfunctional auditor behavior.